Cervicocerebral Computed Tomography Angiography for Older Patients Based on Time to Peak and Number of Time Points to Peak in the Test Bolus Technique. Issue 1 (13th December 2022) - Zeng, Yuli; He, Rong; Ren, Yong; Che, Yilei; Wang, Guiliang
Abstract : Objective: This study sought to optimize image quality and reduce the contrast dose by adjusting contrast agent and normal saline doses used in cervicocerebral computed tomography angiography (CTA) of older patients. Methods: Older patients who underwent cervicocerebral CTA were divided into group A (n = 110) and group B (n = 124). In the angiography scan, patients in group A were injected with 1.0 mL/kg contrast agent, followed by 40 mL saline chaser. In group B, contrast agent and normal saline doses were adjusted based on time to peak and number of time points to peak in the test bolus technique. The CT attenuation values, noise, signal-to-noise ratio, and contrast-to-noise ratio of target arteries and the right transverse sinus were objectively compared. Results: Compared with group A, the contrast retention and artifacts in the right subclavian vein, right brachiocephalic veins, and superior vena cava were significantly decreased in group B. Furthermore, in group B, the noise at the bifurcation of the right common carotid artery increased by 1.7%, and the signal-to-noise ratio of the left middle cerebral artery M1 segment decreased by 6.6%. The contrast dose in group B decreased significantly (18.2%) as compared with group A. Conclusion: Based on time to peak and number of time points to peak with the test bolus, adjusting contrast and normal saline doses in cervicocerebral CTA for older people reduces contrast retention and artifacts in the veins of the injection side. Further, it also decreases the contrast dose needed to obtain image quality that satisfies diagnostic requirements.